2020
DOI: 10.1289/ehp5884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GenX on P-Glycoprotein, Breast Cancer Resistance Protein, and Multidrug Resistance–Associated Protein 2 at the Blood–Brain Barrier

Abstract: BACKGROUND: Ammonium 2,3,3,3-tetrafluoro-2-(heptafluoropropoxy)propanoic acid (GenX) is a replacement for perfluorooctanoic acid in the production of fluoropolymers used in a variety of consumer products. GenX alters fetal development and antibody production and elicits toxic responses in the livers and kidneys of rodents. The GenX effect on the blood-brain barrier (BBB) is unknown. The BBB protects the brain from xenobiotic neurotoxicants and harmful endogenous metabolites. OBJECTIVES: We aimed to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
1
20
0
1
Order By: Relevance
“…For example, low concentrations of tetrabromobisphenol A (TBBPA; a commonly used brominated flame retardant) and GenX (CAS no. 62037-80-3; used as a replacement for perfluorooctanoic acid (PFOA) in consumer products, such as frying pans) have been shown to inhibit BCRP-mediated transport in rat brain capillaries [ 43 , 44 ]. In addition, many commonly used therapeutic drugs inhibit BCRP transporter activity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, low concentrations of tetrabromobisphenol A (TBBPA; a commonly used brominated flame retardant) and GenX (CAS no. 62037-80-3; used as a replacement for perfluorooctanoic acid (PFOA) in consumer products, such as frying pans) have been shown to inhibit BCRP-mediated transport in rat brain capillaries [ 43 , 44 ]. In addition, many commonly used therapeutic drugs inhibit BCRP transporter activity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrity of the BBB can be compromised because of exposures to certain toxicants, such as pesticides, mixed vehicle emissions, and tobacco smoke, as well as certain health conditions including diabetes and neurological disorders reviewed in Neurotoxicity of PFAS in Sensitive Populations , through molecular alterations in barrier function ( Gupta et al, 1999 ; Weiss et al, 2009 ; Mazzone et al, 2010 ; Oppenheim et al, 2013 ; Prasad et al, 2014 , 2015 ; Erdő et al, 2017 ; Suwannasual et al, 2018 ; Martinez and Al-Ahmad, 2019 ). PFAS can disrupt BBB integrity by various mechanisms including disruption of endothelial tight junctions, actin filament remodeling induced by oxidative stress, and decreased activity of efflux transporters ( Qian et al, 2010 ; Wang X. et al, 2011 ; Reistad et al, 2013 ; Cannon et al, 2020 ). Therefore, PFAS exposure may impact access and accumulation of contaminants in the brain, by increasing permeability at the BBB.…”
Section: Pfas Uptake and Accumulation In The Brainmentioning
confidence: 99%
“…Although lipophilicity is important for transmembrane diffusion through the BBB, some compounds that are too lipophilic can be discharged after crossing into the brain by the P-gp efflux transporter ( Abbott, 2002 ; Banks, 2009 ). Cannon et al (2020) isolated rat brain capillaries to assess the effects of Perfluoro (2-methyl-3-oxahexanoic) acid (GenX), a perfluoroether carboxylic acid that was introduced as an alternative for PFOA and PFOS, on the BBB. This study found that GenX decreases the transport activity of P-gp and breast cancer resistance protein (BCRP), two ABC transporters which actively limit endogenous ligands, xenobiotics, and drugs from reaching sensitive target tissues, including the brain.…”
Section: Pfas Uptake and Accumulation In The Brainmentioning
confidence: 99%
“…In enterocytes, excretion of polyphenols towards the intestinal lumen can occur through ATP-binding cassette transporters (ABCs). Other transporters, such as multidrug resistance proteins (MRPs) and monocarboxylate transporters, play a role in the transport of polyphenols to the vascular side [23]. Furthermore, it has been shown that MRP2 and p-glycoprotein play a pivotal role in the efflux of metabolized polyphenols as highlighted in a Caco-2 cell transwell model.…”
Section: Bioavailability and Metabolism Of Flavonolsmentioning
confidence: 99%